Microscale heat transfer in macro geometries - Kong, Kian Shing (2013)
The escalating heat dissipation problem in electronic devices has become the key driver to numerous investigations on new cooling techniques, including the heavily-researched microchannel heat sink. However, literature shows that microscale heat transfer is generally not being applied to macro geometries, which is believed largely due to the fabrication and operational challenges. In present study, experiments were conducted to attain high heat removal capabilities comparable to that of microchannels in a circular channel of conventional size, which was manufactured through conventional techniques. The channel is 20 mm in diameter and 30 mm in length. Inserts of different sizes and profiles were inserted into the flow channel, one at a time, to make the annular flow path small enough to behave like a microchannel. The gap size of the flow channels experimented ranges from 200 to 1000 μm. Experimental results obtained showed that the design was able to achieve a maximum heat transfer coefficient of 79,000 W/m2·K with single-phase water flowing through the annular channel of gap size of 200 μm at Reynolds number of 5600.